Optimalisasi Peran Dewan Pengawas Syariah (DPS) Dalam Menjaga Kepatuhan Syariah Pada Perbankan Syariah di Indonesia - Sumar'in, Sumar'in (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2017)
The challenge of financial globalization impact on Islamic finance businesses to maintain shariah compliance aspects as a means of mistake prevention and possible risks in the real sector. Compliance functions as actions and measures, both are preventive to ensure the policies, rules, systems and procedures, the business activities carried out by the Islamic Bank. The design of this study is library reaserch approach. The result shows that the system of supervision of compliance toward sharia must been done based on the rules by DPS. The functions of DPS on Islamic Banking, normatively must been implemented in accordance with the principles of compliance, the compliance culture, management risk and the values of shariah systems. The existence of DPS really determines the establishment of sharia compliance, which becomes the main unsure in the existence and continuity of syariah financial industry.